ФАКТОРИ ВПЛИВУ НА ПРОЦЕСИ МОДЕРНІЗАЦІЇ ВИЩОЇ ОСВІТИ - Kryazhev, P (Continuing Professional Education: Theory and Practice, 2019)
In article infl uence factors on modernization processes in higher education are considered. The external and internal factors of infl uence on modernization and development of the world higher school are analyzed. It is defi ned that the fi rst fundamental factor of infl uence is scientifi cal and technological progress, and the second factor is the change of labor market. The main internal factor is aspiration of the HEI to increase own autonomy in the conditions of search by the government of new mechanisms of functioning state educational inspectorate.